CT guided minimal invasive oxygen ozone therapy in patients with degenerative changes of lumbosacral spine - Davidović, Kristina (Medicinski podmladak, 2022)
Degenerative spine conditions involve the gradual loss of normal structure and function of the spine over time. They are usually caused by aging, but may also be the result of tumors, infections or arthritis. Pressure on the spinal cord and nerve roots caused by degeneration can be caused by herniated discs. Degenerative disc disease is one of the most common causes of low back and neck pain, and also one of the most misunderstood. Low back pain (LBP) is a common disorder affecting an increasing number of people worldwide, whose diagnosis is focused on the identification of triggering causes. First line therapy usually starts from conservative approaches, whereas second line treatments include a spectrum of minimally invasive techniques, before resorting to more invasive surgical approaches. Among minimally invasive techniques, percutaneous oxygen-ozone injections represent one of the most common and cost-effective procedures. Oxygen-ozone therapy is a minimally invasive treatment for lumbar disc herniation that uses the biochemical properties of the gas mixture of oxygen and ozone. Intradiscal, periradicular or intraarticular ozone therapy is used in patients that do not respond to standard conservative therapies for low back pain due to degenerative disc-induced lumbar disc herniation (LDH) or other degenerative process of nearby structures such as zygapophyseal articulations. All the interventional procedures for low back pain may be guided by ultrasound, computerized tomography or fluoroscopy.
Keywords: Low back pain, Ozone therapy, Periradicular injection, degenerative disk disease